2019
DOI: 10.4067/s0717-95022019000300885
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric Analysis of Bite Mark Patterns Caused by Domestic Dogs ( Canis lupus familiaris ) Using Dental Wax Registers

Abstract: Morphometric analysis of bite mark patterns caused by domestic dogs (Canis lupus familiaris) using dental wax registers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…According to Page et al (2012), even DNA analyzes can suffer from subjective interpretation and confirmation bias under specific conditions, a phenomenon that would also occur in FO when the procedures do not eliminate the context and lead to selective and confirmatory hypotheses "akin to painting the target around an arrow". This phenomenon has been sufficiently reported in bite mark comparisons, and although carefully designed collective and analytical processes and quantitative research on the influence of cognitive bias in FO have been recommended (Page et al, 2012), our review identified only two studies on bite mark evidence (one of them focused on animal bite marks (Toledo-González et al, 2019), the other on bite mark comparisons by using three-dimensional analysis (Dalle Grave et al, 2021)), an insufficiency that has already been reported by Espinoza-Silva et al (2023).…”
Section: Journal Data On Publicationsmentioning
confidence: 99%
“…According to Page et al (2012), even DNA analyzes can suffer from subjective interpretation and confirmation bias under specific conditions, a phenomenon that would also occur in FO when the procedures do not eliminate the context and lead to selective and confirmatory hypotheses "akin to painting the target around an arrow". This phenomenon has been sufficiently reported in bite mark comparisons, and although carefully designed collective and analytical processes and quantitative research on the influence of cognitive bias in FO have been recommended (Page et al, 2012), our review identified only two studies on bite mark evidence (one of them focused on animal bite marks (Toledo-González et al, 2019), the other on bite mark comparisons by using three-dimensional analysis (Dalle Grave et al, 2021)), an insufficiency that has already been reported by Espinoza-Silva et al (2023).…”
Section: Journal Data On Publicationsmentioning
confidence: 99%